NATURAL HISTORICAL GEOGRAPHY OF THE KHOREZM OASIS - N.S.P Matyaqubova Nozima Maksatbayevna (Scholars Digest Publishing, 2025)
This article discusses the natural and geographical conditions of the Khorezm oasis, the Amu Darya riverbed and its historical formation processes, ancient irrigation systems, and their study based on archaeological research. The geological, climatic, and hydrographic features of the Amu Darya basin, its connection with the Aral Sea, as well as the role of irrigation systems in the development of ancient Khorezm culture are analyzed. The article considers the results of the Khorezm archaeological expedition led by S.P. Tolstov, canals, fortresses, and other historical monuments identified using aerial methods as an important source.
Keywords: Khorezm oasis, Amu Darya, Aral Sea, irrigation systems, ancient ozans, archaeological research, S.P. Tolstov, Uzboy, Akchadarya, Sarikamishboy, Kaltaminor, Suvyorgan, Amirabad culture.